Reckless : an It Girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2006)
Popular Gossip Girl character Jenny Humphrey is making a splash at Waverly Academy, an elite boarding school in New York horse country where glamorous rich kids don't let the rules get in the way of an excellent time. It's less than a semester into school, but Jenny's already become notorious, just like Tinsley Carmichael - who won't give up her Waverly "it girl" crown without a fight.
Ages 15 and up.
Keywords: Boarding school students -- Fiction; Teenage girls -- Fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; Conduct of life -- Fiction; New York (State) -- Fiction